Comparative ultrasound study of gastric emptying between an isotonic solution and a nutritional supplement - Bisinotto, Flora Margarida Barra [UNESP]; Silveira, Luciano Alves Matias da; Rossi, Tiago Caneu; Martins, Laura Bisinotto; Zago, Gustavo Palis; Mendonça, Mariana Andrade Lopes (Elsevier, 2019)
Background and objectives: Preoperative fasting may lead to undesirable effects in the surgical patient in whom there is a stimulus to ingesting clear liquids until 2 hours before anesthesia. The aim of this study was to evaluate the gastric emptying of two different solutions using ultrasound. Methods: In a prospective, randomized, blind study, 34 healthy volunteers ingested 200 mL of two solutions without residues in two steps: an isotonic solution with carbohydrates, electrolytes, osmolarity of 292 mOsm.L ‐1 , and 36 kcal; and other nutritional supplementation with carbohydrates, proteins, electrolytes, osmolarity of 680 mO.L ‐1 , and 300 kcal. After 2 hours, a gastric ultrasound was performed to assess the antrum area and gastric volume, and the relation of gastric volume to weight (vol.w ‐1 ), whose value above 1.5 mL.kg ‐1 was considered a risk for bronchoaspiration. A p‐value < 0.05 was considered statistically significant. Results: There was a significant difference between all parameters evaluated 2 hours after the ingestion of nutritional supplementation compared to fasting. The same occurred when the parameters between isotonic solution and nutritional supplementation were compared 2 hours after ingestion. Only one patient had vol.w ‐1 < 1.5 mL.kg ‐1 2 hours after ingestion of nutritional supplementation; and only one had vol.w ‐1 > 1.5 mL.kg ‐1 after ingestion of isotonic solution. Conclusion: This study demonstrated that gastric emptying of equal volumes of different solutions depends on their constitution. Those with high caloric and high osmolarity, and with proteins present, 2 hours after ingestion, increased the gastric volumes, which is compatible with the risk of gastric aspiration.
Estudo comparativo do esvaziamento gástrico entre uma solução isotônica e um suplemento nutricional por meio da ultrassonografia
Keywords: Bronchoaspiration; Gastric ultrasound; Preoperative fasting